2018
DOI: 10.1111/cen.13898
|View full text |Cite
|
Sign up to set email alerts
|

A new ultrasound nomogram for differentiating benign and malignant thyroid nodules

Abstract: Summary Objective The Thyroid Imaging Reporting and Data System (TI‐RADS) is commonly used for risk stratification of thyroid nodules. However, this system has a poor sensitivity and specificity. The aim of this study was to build a new model based on TI‐RADS for evaluating ultrasound image patterns that offer improved efficacy for differentiating benign and malignant thyroid nodules. Design and Patients The study population consisted of 1092 participants with thyroid nodules. Measurements The nodules were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…This may reflect that ultrasonography is less accurate at assessing shape, the larger the thyroid nodule is. Conversely, our study identified ill-defined border as a predictor of malignancy, similar to a previous study ( 19 ), but this factor is assigned 0 point in ACR TI-RADS. Our model and associated nomogram may be clinically easier to use than ACR TI-RADS and more accurate for thyroid nodules > 4 cm.…”
Section: Discussionsupporting
confidence: 86%
“…This may reflect that ultrasonography is less accurate at assessing shape, the larger the thyroid nodule is. Conversely, our study identified ill-defined border as a predictor of malignancy, similar to a previous study ( 19 ), but this factor is assigned 0 point in ACR TI-RADS. Our model and associated nomogram may be clinically easier to use than ACR TI-RADS and more accurate for thyroid nodules > 4 cm.…”
Section: Discussionsupporting
confidence: 86%
“…Chen et al. ( 50 ) recently provided evidence that age, margin, shape, echogenic foci, echogenicity, and nodule halo sign are independent risk factors, whereas Liang et al. ( 51 ) reported that age has no significant relevance with PTC diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The emerging issue of thyroid cancer in adult TM patients indicates the need for preventive measures, yearly thyroid US surveillance and careful follow-up. Recently Chen et al, 107 based on the Thyroid Imaging Reporting and Data System (TI-RADS), built a new model using a combination of ultrasound patterns including margin, shape, echogenic foci, echogenicity and nodule halo sign with age to differentiate benign and malignant thyroid nodules, which had high sensitivity and specificity.…”
Section: Conclusion Hypothyroidism Is a Clinical Disordermentioning
confidence: 99%